The Mystery of Death in Robert Frost's Poems - Eka Dahlia Ningrum; Masulah - (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2016)
This study analyzed Robert Frost’s poems. There are three purpose of this study: analyze about figures of speech and theme death in Robert Frost’s poems. The writer was choosing Robert Frost’s because he developed a new style of poetry that was metrically precise but which sounded like ordinary American speech. His poetry was full of sentimental expressions about his personal life and conduct. Besides, his poems were simple and profound. He also wrote simple stories about everyday people, often inhabitants of rural New England. Robert Frost wrote extraordinary prose, using simple and direct language; his poems contain symbolism, hidden meanings, sounds, rhyme, meter, metaphors and more. The title of three poems were “Fire and Ice” , “In a Disused Graveyard” , “The Death of The Hired Man” that taken data from “Classic Poetry Series of Robert Frost Poems” publisher. The method used to analyzed the analysis data was Qualitative Method. This method was chosen because the object if this study does not treat object, and the object can only researched by an observation and description up to the writer’s point of view and match with theory. The result of the study shows that many of figures of speech were used on three of Robert Frost’s poems. They were Metaphor, Symbol, Hyperbole, Assonance, Anaphora, Personification, Paradox, Simile, Antithesis, Alliteration, Irony, Synecdoche and theme death could open the meaning poem as “Fire and Ice”, tells about the end of world between fire or ice. “In a Disused Graveyard”, tells about the people won’t to die. “The Death of The Hired Man” tells about the pity old man suddenly die in his employer’s home.